Bimbingan Teknis Akuntansi Pemerintahan dengan Modul dan Kertas Kerja Praktik Bagi Guru dan Siswa SMK Negeri 3 Padang - Andriani, Wiwik; Yentifa, Armel; Zahara, Zahara; Hasanah, Anggun Desmita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Understanding Government Accounting concepts is a competency that must be mastered by teachers and students at Vocational High Schools (SMK) as a basis for carrying out learning activities, especially in the field of Government Accounting. In its implementation, it is still necessary to improve the understanding of teachers and students related to the concept of Government Accounting. SMK Negeri 3 Padang, which is a partner in this service, faces obstacles in understanding Government Accounting. This service aims to provide understanding and skills to teachers and students at SMK Negeri 3 Padang about government accounting through technical guidance activities by making practical work modules for teachers and students in accordance with applicable government accounting standards in Indonesia. Activities carried out in this technical guidance are discussions, making modules and practical work on Government Accounting, technical guidance and training, as well as more in-depth mentoring of teachers and students. The results showed that there was an increase in participants' understanding from 70% to 90% based on the tests conducted. With this activity, it is expected to improve the competence of teachers and accounting students of SMK Negeri 3 Padang related to Government Accounting.